Investigation of structural, mechanical, dynamic, electronic and optical properties of seleno-germanates A2GeSe4 (A = Mg, Ca and γ-Sr) from first principles. (March 2020) - Barde, Abdu; Joubert, Daniel P.
Abstract: In this work we systematically investigated the structural, mechanical, electronic, dynamical and optical properties of A 2 GeSe 4 (A = Mg, Ca and Sr) seleno-germanate compounds by density functional calculations. Synthesis of Mg 2 GeSe 4 and Sr 2 GeSe 4 have been reported, while Ca 2 GeSe 4 is a hypothetical compound. The lattice parameters, equilibrium volume, lattice constants, cohesive and formation energies and bulk moduli were calculated. Our calculated lattice parameters and equilibrium volumes are in reasonable agreement with available experimental data. Elastic constants satisfy the Born stability criteria, confirming mechanical stability of all three compounds. Vibrational properties, studied using a finite displacement method, revealed no negative phonon frequencies across the Brillouin zone and therefore the compounds are dynamically stable. Hybrid functional and many-body perturbation theory were employed for the study of the electronic band structure and optical properties. Band structure results suggest that Mg 2 GeSe 4 and Ca 2 GeSe 2 are indirect band gap and Sr 2 GeSe 4 a direct band gap semiconductor. The Bethe–Salpeter equation (BSE) was solved to include excitonic effect for an accurate description of optical properties. Optical absorption spectra show significant optical anisotropy. Band gaps estimated from BSE are 2.58, 2.30 and 2.86 eV for Mg 2 GeSe 4, Ca 2 GeSe 4 and Sr 2 GeSe 4 respectively. The calculated band gaps suggests that Mg 2 GeSe 4, Ca 2 GeSe 4 and Sr 2 GeSe 4 are semiconductors with potential to absorbed light in the ultra-violet and upper visible regions. The computed band edges from a Mulliken's analysis suggest that the A 2 GeSe 4 compounds have suitable conduction band minima (CBM) potentials of − 0.97, − 1.45 and − 1.86 V, respectively, versus the normal hydrogen electrode (NHE) for water reduction. The calculated BSE gaps and CBM minima of A 2 GeSe 4 suggest that they are suitable candidates that can be exploited for applications in non-linear optics, photovoltaic (multi-junction solar cells) and visible response photo-catalytic materials.